Forward Guidance under Disagreement - Evidence from the Fed's dot projections - Gunda-Alexandra Detmers (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
This paper compares the effectiveness of date- and state-based forward guidance issued by the Federal Reserve since mid-2011 accounting for the influence of disagreement within the FOMC. I find that the Fed's forward guidance reduces the sensitivity of interest rates to macroeconomic news. The sensitivity shrinkage is stronger in the case of date-based forward guidance due to its unconditional nature. Yet, high levels of disagreement as published through the FOMC's dot projections since 2012 partially restore sensitivity to macroeconomic news. Thus, disagreement appears to lower the information content of forward guidance and to weaken the Fed's commitment as perceived by financial markets.
Keywords: E52; E58; E43; 330